ANALYSIS OF STAKEHOLDER ROLES IN THE SUSTAINABILITY OF RED RICE FARMING IN JATILUWIH VILLAGE - I Gusti Ayu Agung Bintang Setya Maharani; Ni Nyoman Reni Suasih (Adisam Publisher, 2025)
This study aims to analyze the roles of stakeholders in supporting the sustainability of red rice farming in Jatiluwih Village, Tabanan Regency, Bali, which is recognized as a sustainable agricultural area through the Subak system acknowledged by UNESCO as a world cultural heritage. The research adopts a descriptive quantitative approach using a survey method involving six main actors: farmers, the Subak organization, the agricultural office, the private sector, the traditional village (desa adat), and the Subak cooperative. Analysis was conducted using the MACTOR method to identify the influence and relationships among stakeholders and their alignment with sustainability goals in farming practices. The results show that active stakeholder involvement plays a significant role in supporting the economic, social, and environmental dimensions of red rice farming systems. Collaboration among these actors contributes to increased farmers’ income, environmental conservation, and the strengthening of local cultural values. Continuous synergy between the government, traditional communities, and the private sector is required to preserve the traditional agricultural system while improving the welfare of the local population.